The Existence and Development of Compilation of Sharia Economic Law (KHES) and Its Urgency in Resolving Sharia Economic Law Disputes in Indonesia - Nurjamil Nurjamil (PT. Anagata Sembagi Education, 2024)
This research delves into Sharia Economic Law (KHES) as a regulatory framework for resolving Sharia economic disputes in Indonesia, examining its historical, political, and philosophical dimensions alongside its practical urgency. Employing a qualitative literature review, it analyzes secondary data from various sources such as books, journals, and research findings to elucidate KHES's development and its significance in dispute resolution. KHES was established in response to Law No. 3 of 2006, which expanded the jurisdiction of Religious Courts in Sharia economic matters. It harmonizes diverse scholarly opinions from traditional sources like fiqh texts and fatwas issued by DSN-MUI, providing a legal compass for Muslim economic activities. Despite not being formally ranked within Indonesia's legislative hierarchy, KHES, born out of PERMA No. 2 of 2008, serves as a key legal reference for Religious Court judgments and informs legal deliberations on Sharia economic issues. Efforts are underway to potentially elevate its status to that of Government Regulations, ensuring its broader enforceability within the Indonesian legal system.